Steel wire and machine parts
Patent Information
- Application Number
- JP2024544539
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2024-03-29
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2044-03-29
AI Technical Summary
【0008】 本開示によれば、強度が高く、かつ冷間鍛造での成形性に優れ、成形後の時効熱処理を省略しても高い耐力と永久伸びの抑制が得られる機械部品の製造に好適な鋼線、並びに機械部品が提供される。
Smart Images

Figure 0007610175000001 
Figure 0007610175000002 
Figure 0007610175000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to steel wire and machine parts. [Background technology]
[0002] High-strength materials are required for machine parts such as steel bolts and screws in order to reduce their weight and size. Conventionally, these machine parts are manufactured by softening machine structural steel wire rods containing C, Mn, Cr, Mo, etc. through spheroidizing annealing, forming them into a desired shape through cold heading and rolling, and then quenching and tempering to impart strength.
[0003] Because heat treatments such as spheroidizing annealing and quenching and tempering increase manufacturing costs and CO2 emissions, a non-tempered bolt is known that omits these heat treatments and instead increases strength by adjusting the composition and rapidly cooling the wire rod, then drawing it to create a bolt with added strength. 2. Description of the Related Art Various wire rods and steel wires for producing machine parts such as non-heat treated bolts have been proposed (see, for example, Patent Documents 1 to 5). [Prior art documents] [Patent documents]
[0004] Patent document 1: Japanese Patent Application Laid-Open No. 2-166229 Patent Document 2: International Publication No. 2016 / 121820 Patent Document 3: International Publication No. 2017 / 122830 Patent Document 4: International Publication No. 2018 / 008698 Patent Document 5: JP 2021-183710 A Summary of the Invention [Problem to be solved by the invention]
[0005] Non-tempered bolts are made by forming steel wire whose strength has been increased by wire drawing. As the strength of the steel wire increases, the mold becomes more susceptible to damage and wear during forming, and the product becomes more susceptible to processing cracks, making it difficult to apply this to high-strength bolts. In addition, conventional non-tempered bolts have a high dislocation density, which results in low bolt strength and large permanent elongation. To improve this, it is necessary to add a bluing process in which the bolt is held at 300 to 400°C after being formed into mechanical parts such as bolts.
[0006] An object of the present disclosure is to provide a steel wire suitable for producing mechanical parts, which has high strength and excellent formability in cold forging, and which provides high yield strength and suppressed permanent elongation even when bluing heat treatment after forming is omitted, and a mechanical part. [Means for solving the problem]
[0007] The above problems are solved by the following means. <1> In mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0~0.20%, Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0-0.30%, Sb: 0 to 0.005%, and Ca: 0 to 0.0050%, and the balance being Fe and impurity elements, The contents of C, Si, Mn, Cr, Ni, Mo, and Cu in mass% are (C%), (Si%), (Mn%), (Cr%), (Ni%), (Mo%), and (Cu%), respectively. (I) the chemical composition is, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010 to 0.0150%, and O: 0.003% or less, with the balance being Fe and impurity elements, DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)), (II) the chemical composition is, in mass%, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0~0.20%, Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0-0.30%, Sb: 0 to 0.005%, and Ca: 0 to 0.0050%, and the B content is less than 0.0003%, DI = 0.311 × (C%) 0.5 ×(1+0.64×(Si%))×(1+4.10×(Mn%))×(1+2.33×(Cr%))×(1+0.25×(Ni%))×(1+3.14×(Mo%))×(1+0.27×(Cu%)), (III) the chemical composition is, in mass%, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0~0.20%, Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0-0.30%, Sb: 0 to 0.005%, and Ca: 0 to 0.0050%, and the B content is 0.0003 to 0.0050%, DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)) × (1 + 2.33 × (Cr%)) × (1 + 0.25 × (Ni%)) × (1 + 3.14 × (Mo%)) × (1 + 0.27 × (Cu%)) × (1 + 1.5 × (0.90 - (C%))). DI is between 1.40 and 4.50, When the diameter of the steel wire is D, the total area ratio of ferrite and martensite in the metal structure at a 1 / 4D part having a depth of 1 / 4D from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire is 30.0% or less, When F1 = (C%) + 0.10 × (Si%) + 0.18 × (Mn%) + 0.20 × (Cr%), the tensile strength is 860 × F1 + 450 MPa or more and 920 × F1 + 670 MPa or less, (tensile strength - 0.2% yield strength) / uniform elongation is 20 + 25 × (C%) or less, A steel wire having a reduction ratio of 66-48×(C%) or more. <2> The total area ratio of bainite and pearlite in the metal structure at the 1 / 4D part is 70.0% or more, <1> The steel wire according to claim 1. <3> A mechanical component having a cylindrical shaft portion, In mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0~0.20%, Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0-0.30%, Sb: 0 to 0.005%, and Ca: 0 to 0.0050%, The balance has a chemical composition consisting of Fe and impurity elements, The contents of C, Si, Mn, Cr, Ni, Mo, and Cu in mass% are (C%), (Si%), (Mn%), (Cr%), (Ni%), (Mo%), and (Cu%), respectively. (I) the chemical composition is, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010 to 0.0150%, and O: 0.003% or less, with the balance being Fe and impurity elements, DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)), (II) the chemical composition is, in mass%, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0~0.20%, Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0-0.30%, Sb: 0 to 0.005%, and Ca: 0 to 0.0050%, and the B content is less than 0.0003%, DI = 0.311 × (C%) 0.5 ×(1+0.64×(Si%))×(1+4.10×(Mn%))×(1+2.33×(Cr%))×(1+0.25×(Ni%))×(1+3.14×(Mo%))×(1+0.27×(Cu%)), (III) the chemical composition is, in mass%, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0~0.20%, Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0-0.30%, Sb: 0 to 0.005%, and Ca: 0 to 0.0050%, and the B content is 0.0003 to 0.0050%, DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)) × (1 + 2.33 × (Cr%)) × (1 + 0.25 × (Ni%)) × (1 + 3.14 × (Mo%)) × (1 + 0.27 × (Cu%)) × (1 + 1.5 × (0.90 - (C%))). DI is between 1.40 and 4.50, When the diameter of the shaft portion is d, a total area ratio of ferrite and martensite in a metal structure at a 1 / 4d portion that is a depth of 1 / 4d from the surface of the shaft portion in a cross section perpendicular to the longitudinal direction of the shaft portion is 30.0% or less, The shaft portion is When F1 = (C%) + 0.10 × (Si%) + 0.18 × (Mn%) + 0.20 × (Cr%), the tensile strength is 860 × F1 + 430 MPa or more and 920 × F1 + 660 MPa or less, (tensile strength - 0.2% yield strength) / uniform elongation is 38 + 25 × (C%) or less, 0.2% yield strength / tensile strength is 0.97-0.10×(C%) or more; A mechanical part with a reduction ratio of 65-48×(C%) or more. <4> The total area ratio of bainite and pearlite in the metal structure at the 1 / 4d part is 70.0% or more. <3> A mechanical part as described in. Effect of the Invention
[0008] According to the present disclosure, there are provided a steel wire and a machine component suitable for manufacturing machine components, which have high strength and excellent formability in cold forging, and can obtain high yield strength and suppressed permanent elongation even when aging heat treatment after forming is omitted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The wire according to the present disclosure will now be described. In this disclosure, a numerical range expressed using "~" means a range that includes the numerical values before and after "~" as the lower and upper limits. However, when the numerical values before and after "~" are followed by "more than" or "less than," the numerical range does not include these numerical values as the lower or upper limit. The content of an element in a chemical composition may be expressed by adding the "amount" to the element symbol (for example, C amount, Si amount, etc.). With respect to the contents of elements in chemical compositions, "%" means "mass %." When the content of an element in a chemical composition is described as "0~", it means that the element does not have to be contained. The term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. The "surface" of a steel wire means the "outer surface." The "central axis" of a steel wire means an imaginary line that passes through the center point of a cross section perpendicular to the longitudinal direction of the steel wire and extends in the longitudinal direction (axial direction). "1 / 4D" is synonymous with "D / 4".
[0010] [Steel wire] The steel wire according to the present disclosure has a chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010 to 0.0150%, and O: Contains 0.003% or less, with the balance being Fe and impurity elements; The contents of C, Si, Mn, and Cr in mass% are (C%), (Si%), (Mn%), and (Cr%), respectively, and DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)), the DI is 1.40 or more and 4.50 or less, When the diameter of the steel wire is D, the total area ratio of ferrite and martensite in the metal structure at a 1 / 4D part having a depth of 1 / 4D from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire is 30.0% or less, If F1 = (C%) + 0.10 × (Si%) + 0.18 × (Mn%) + 0.20 × (Cr%), The tensile strength is 860×F1+450MPa or more and 920×F1+670MPa or less, (tensile strength - 0.2% yield strength) / uniform elongation is 20 + 25 × (C%) or less, The aperture is 66-48×(C%) or more.
[0011] The inventors of the present disclosure have studied the effects of a steel wire and its mechanical properties on the formability when processed into mechanical parts and on the characteristics of the mechanical parts, and have found that by setting the components of the steel wire within a specific range, by configuring the structure of the steel wire to have a structure in which the area ratio of ferrite and martensite is suppressed, and by reducing the (tensile strength - 0.25% proof stress) / uniform elongation of the steel wire and increasing the reduction in area, it is possible to obtain a bolt with excellent formability and a high bolt proof strength ratio and suppression of permanent elongation after processing into a non-tempered bolt. As mentioned above, since non-thermal refined parts are given strength before forming, there have been issues with their application to high-strength parts due to reduced die life and processing cracks in the product. When the steel wire structure has a high area ratio of martensite, for example in processing that causes high strain, such as processing the head of a bolt, the strength of the part increases due to work hardening, and the deformation resistance during processing increases. The inventors of the present disclosure have found that reducing the (tensile strength-0.25% proof stress) / uniform elongation of a steel wire reduces work hardening, suppresses work hardening in high strain processing such as bolt head processing, and reduces the load on the die. Furthermore, they have found that increasing the drawing of the steel wire can suppress processing cracks in non-heat-treated parts.
[0012] When the area ratio of the ferrite structure in steel wire is high, the yield strength ratio of the mechanical parts is low. Non-tempered bolts have a high dislocation density because their strength is imparted by wire drawing. If there are many mobile dislocations, they will undergo plastic deformation with small strain, lowering the elastic limit and resulting in low yield strength. In order to increase the yield strength of steel with high dislocation density, it is effective to fix the solute carbon and nitrogen contained in the steel to the dislocations to suppress their movement. If the area ratio of the martensite structure in the steel wire is high, processing cracks may occur when the steel wire is formed into a mechanical part, and the yield strength ratio of the mechanical part may be reduced.
[0013] Conventional non-tempered bolts use a heat treatment called bluing, which involves holding the bolt at 300 to 400°C to fix carbon to the dislocations, thereby suppressing their movement and increasing the strength of the bolt. The inventors of the present disclosure have found that by reducing the area ratio of ferrite or martensite in the structure of a steel wire and setting the (tensile strength-0.25% proof stress) / uniform elongation of the steel wire within a specific range, the proof stress ratio of a non-thermal-treated mechanical part can be increased and permanent elongation can be suppressed without performing a bluing treatment. This is presumably because the solute carbon concentration after wire drawing is high, so that carbon is fixed to mobile dislocations even without heating to the bluing treatment temperature of 300 to 400°C, suppressing the movement of dislocations, and a high proof stress ratio can be obtained by reducing work hardening.
[0014] <Chemical composition> The chemical composition of the steel wire according to the present disclosure is, as essential elements, in mass%: C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010 to 0.0150%, and O: Contains 0.003% or less, with the balance being Fe and impurity elements; The contents of C, Si, Mn, and Cr in mass% are (C%), (Si%), (Mn%), and (Cr%), respectively, and DI = 0.311 × (C%) 0.5 When calculated as × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)), the DI is 1.40 or greater and 4.50 or less.
[0015] The steel wire according to the present disclosure may contain other optional elements as necessary. When the steel wire according to the present disclosure contains the optional elements, When the B content is less than 0.0003%, DI = 0.311 × (C%) 0.5 ×(1+0.64×(Si%))×(1+4.10×(Mn%))×(1+2.33×(Cr%))×(1+0.25×(Ni%))×(1+3.14×(Mo%))×(1+0.27×(Cu%)), When the B content is 0.0003 to 0.0050%, DI = 0.311 × (C%) 0.5×(1+0.64×(Si%))×(1+4.10×(Mn%))×(1+2.33×(Cr%))×(1+0.25×(Ni%))×(1+3.14×(Mo%))×(1+0.27×(Cu%))×(1+1.5×(0.90-(C%))). Regardless of the B content, the DI is 1.40 or more and 4.50 or less. If the DI is less than 1.40, the strength and yield strength ratio of the mechanical part will be low. The preferred DI is 1.60 or more. If the DI exceeds 4.50, the workability will be deteriorated. The preferred DI is 4.00 or less, and more preferably 3.00 or less.
[0016] C: 0.08 to 0.80% C is added to ensure the strength required for mechanical parts. If the C content is less than 0.08%, it is difficult to ensure the necessary strength for mechanical parts. On the other hand, if the C content exceeds 0.80%, ductility, toughness, and cold forgeability deteriorate. Therefore, the C content is set to 0.08 to 0.80%. The lower limit of the C content is 0.08%, preferably 0.15%, and more preferably 0.20%, and the upper limit of the C content is 0.80%, preferably 0.75%, and more preferably 0.70%. The preferred C content for achieving high strength, ductility, toughness, and cold workability is 0.15 to 0.75%, and more preferably 0.20 to 0.70%.
[0017] Silicon: 0.03 to 1.50% Silicon functions as a deoxidizing element and is an effective element for imparting necessary strength to mechanical components. If the amount of silicon is less than 0.03%, these effects are insufficient. If the amount of silicon exceeds 1.50%, the ductility and toughness of the mechanical components deteriorate, and the deformation resistance of the steel wire increases, deteriorating the cold forgeability. Therefore, the amount of silicon is set to 0.03 to 1.50%. The amount of silicon is preferably 0.05 to 1.00%, and more preferably 0.10 to 0.60%.
[0018] Mn: 0.50-2.00% Mn is an element necessary to impart necessary strength to mechanical parts. If the Mn content is less than 0.50%, the effect is insufficient. If the Mn content exceeds 2.00%, the toughness of the mechanical parts is deteriorated, and the deformation resistance of the steel wire increases, deteriorating the cold forgeability. Therefore, the Mn content is set to 0.50-2.00%. The Mn content is preferably 0.70-1.50%, and more preferably 0.90-1.20%.
[0019] P:0.050% or less P is contained in steel wire as an impurity. Since P segregates at the grain boundaries of mechanical components and deteriorates toughness, it is desirable to reduce the P content. For this reason, the upper limit of the P content is set to 0.050%. A preferable upper limit of the P content is 0.020%, and a more preferable upper limit is 0.015% or less. The lower limit of the P content is preferably 0% (i.e., no P is contained), but from the viewpoint of reducing the dephosphorization cost, it may be more than 0% (or 0.0001% or more).
[0020] S: 0.050% or less S is contained in the steel wire as sulfides such as MnS. These sulfides improve the machinability of wire rod or drawn steel wire. If the S content exceeds 0.050%, the cold heading property of the steel wire is deteriorated and the toughness of mechanical parts is deteriorated. For this reason, the upper limit of the S content is set to 0.050%. A preferable upper limit of the S content is 0.030%. A more preferable upper limit is 0.015%. Note that the lower limit of the S content may be more than 0% (or 0.001% or more) from the viewpoint of reducing the desulfurization cost.
[0021] Al: 0.005 to 0.080% Al functions as a deoxidizing element, and also has the effect of forming AlN to refine crystal grains and improve the toughness of mechanical parts. It also has the effect of fixing solute N, suppressing dynamic strain aging, and reducing deformation resistance. If the Al content is less than 0.005%, these effects are insufficient. If the Al content exceeds 0.080%, the effects become saturated and manufacturability may decrease. Therefore, the Al content is set to 0.005 to 0.080%. The Al content is preferably 0.010 to 0.065%, and more preferably 0.020 to 0.055%.
[0022] N: 0.0010~0.0150% N forms nitrides with Al, Ti, Nb, V, etc., refines crystal grains, and has the effect of improving the toughness of mechanical parts. If the N content is less than 0.0010%, the amount of nitrides precipitated is insufficient, and the effect cannot be obtained. If the N content exceeds 0.0150%, the deformation resistance of the steel wire increases due to dynamic strain aging caused by solute N, and the workability deteriorates. Therefore, the N content is set to 0.0010 to 0.0150%. The N content is preferably 0.0020 to 0.0100%, and more preferably 0.0025 to 0.0060%.
[0023] O: 0.003% or less O is an impurity and is inevitably contained in steel. If the O content exceeds 0.003%, coarse oxides are formed, which may reduce fatigue strength, so the O content is limited to 0.003% or less. The preferred upper limit of the O content is 0.002%.
[0024] Remainder: Fe and impurity elements In the chemical composition of the steel wire according to the present disclosure, the balance is Fe and impurity elements (which may be referred to as "impurities" as appropriate in the present disclosure). Here, the term "impurities" refers to components contained in raw materials or components mixed in during the manufacturing process and not intentionally contained. Furthermore, impurities also include components that are intentionally contained but are contained in an amount that does not affect the performance of the steel wire according to the present disclosure obtained by drawing a wire rod.
[0025] Moreover, the steel wire according to the present disclosure may contain, in mass %, one or more elements selected from the group consisting of the following Groups A to D, in place of a portion of Fe.
[0026] [Group A] Ti: 0.050% or less, and B: 0.0050% or less of one or two selected from the group consisting of
[0027] Ti: 0.050% or less Ti functions as a deoxidizing element and has the effect of refining crystal grains to improve workability. If the Ti content exceeds 0.050%, these effects are saturated and coarse oxides or nitrides are generated, which may deteriorate the fatigue strength of mechanical parts. Therefore, if Ti is contained, the Ti content is preferably more than 0 and 0.050%. The Ti content is preferably 0.003 to 0.050%, and more preferably 0.007 to 0.040%.
[0028] B: 0.0050% or less B has the effect of suppressing ferrite. If the B content exceeds 0.0050%, carbides are generated at grain boundaries, which may deteriorate wire drawability. Therefore, when B is contained, the B content is preferably more than 0 and 0.0050%. The B content is preferably 0.0003 to 0.0050%, and more preferably 0.0008 to 0.0030%.
[0029] [Group B] Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, and V: 0 to 0.20% of one or more selected from the group consisting of
[0030] Cr:1.50% or less Cr is an element necessary to impart necessary strength to mechanical parts. If the Cr content exceeds 1.50%, the martensite fraction increases, deteriorating workability and increasing the deformation resistance of the steel wire, deteriorating cold forgeability. Therefore, the Cr content is set to 1.50% or less. The Cr content is preferably 0.05 to 0.80%, and more preferably 0.10 to 0.50%.
[0031] Mo: 0.50% or less Mo has the effect of imparting necessary strength to mechanical parts. If the Mo content exceeds 0.50%, the alloy cost increases, and the deformation resistance of the steel wire increases, deteriorating the cold forgeability. Therefore, when Mo is contained, the Mo content is preferably more than 0 and 0.50%. The Mo content is preferably 0.03 to 0.35%, and more preferably 0.05 to 0.25%. The Mo content may be 0.15% or less.
[0032] Nb: 0.050% or less Nb has the effect of increasing the strength of mechanical parts by precipitating carbides and nitrides, the effect of improving toughness by refining crystal grains, the effect of reducing solute N and reducing deformation resistance, etc. If the Nb content exceeds 0.050%, the effect is saturated and the cold forgeability may deteriorate. Therefore, when Nb is contained, the Nb content is preferably more than 0 and 0.050%. The Nb content is preferably 0.001 to 0.040%. The Nb content is more preferably 0.005 to 0.030%.
[0033] V:0.20% or less V has the effect of precipitating carbides and nitrides to increase the strength of mechanical parts. If the V content exceeds 0.20%, the alloy cost increases. Therefore, when V is contained, the V content is preferably more than 0 and 0.20%. The V content is preferably in the range of 0.01 to 0.15%. The V content may be 0.10% or less.
[0034] [Group C] Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0 to 0.30%, and Sb: 0 to 0.005%
[0035] Cu: 0.50% or less Cu precipitates finely, imparting necessary strength to mechanical parts and improving corrosion resistance. If the Cu content exceeds 0.50%, hot ductility deteriorates and surface defects are likely to occur. Therefore, if Cu is contained, the Cu content should be more than 0 and 0.50%. The Cu content is preferably 0.02 to 0.30%. The Cu content may be 0.20% or less.
[0036] Ni: 0.70% or less Ni has the effect of improving corrosion resistance. If the Ni content exceeds 0.70%, the alloy cost increases. Therefore, when Ni is contained, the Ni content is preferably more than 0 and 0.70%. The Ni content is preferably 0.02 to 0.50%, and more preferably 0.05 to 0.30%. The Ni content may be 0.25% or less.
[0037] Sn: 0.30% or less Sn has the effect of improving corrosion resistance. If the Sn content exceeds 0.30%, the ductility decreases and the cold workability deteriorates, so the Sn content is limited to 0.30% or less. The preferred upper limit of the Sn content is 0.20%.
[0038] Sb: 0.005% or less Sb has the effect of improving corrosion resistance. If the Sb content exceeds 0.005%, the ductility decreases and the cold workability deteriorates, so the Sb content is limited to 0.005% or less. The preferred upper limit of the Sb content is 0.004%, and the more preferred upper limit is 0.003%. The Sb content may be 0.002% or less.
[0039] [Group D] Ca:0.0050% or less Ca is added as a deoxidizing element. Ca has the effect of making oxides finer and improving fatigue strength. If the Ca content exceeds 0.0050%, ductility decreases and cold workability deteriorates, so the Ca content is limited to 0.0050% or less. The preferred upper limit of the Ca content is 0.0040%, and the more preferred upper limit is 0.0030%.
[0040] <Metal structure> Next, the metal structure of the steel wire according to the present disclosure will be described. In the metal structure of the steel wire according to the present disclosure, the total area ratio of ferrite and martensite at a depth of 1 / 4D from the surface (outer peripheral surface) of the steel wire in a cross section (C cross section) perpendicular to the longitudinal direction of the steel wire is 30.0% or less. If the total area ratio of ferrite and martensite exceeds 30.0%, the workability deteriorates and the yield strength ratio of mechanical parts decreases. The total area ratio of ferrite and martensite is preferably 20.0% or less, more preferably 10.0% or less. In addition, the remainder of the metal structure in the 1 / 4D portion is preferably bainite and / or pearlite. If the total area ratio of bainite and pearlite is 70.0% or more, the workability is improved and the yield strength ratio of the mechanical part is increased. The total area ratio of bainite and pearlite is preferably 80.0% or more, and more preferably 90.0% or more.
[0041] (Method of measuring metal structure) For microstructural observation, two samples are taken from positions 50 mm apart in the axial direction of the steel wire, the cross section perpendicular to the central axis of each steel wire sample (C section) is mirror-polished, and then etched with picral, and the 1 / 4D section is observed. First, the C-section of the steel wire to be measured is mirror-polished and then etched with picral (a solution of 5% picric acid and 95% ethanol) to reveal the structure. Next, in the 1 / 4D section, four locations are taken at 90° intervals in the circumferential direction, and a microstructure photograph of an area of 20 μm x 20 μm or more at each location is taken at a magnification of 5000 times using a field emission scanning electron microscope (FE-SEM). A structure that does not contain carbides within the grains is considered to be ferrite or martensite.
[0042] The metal structure may include bainite, pearlite, martensite, and ferrite. A structure that does not contain carbides in the grains is ferrite or martensite. A structure other than ferrite or martensite is bainite or pearlite. Therefore, structures other than ferrite or martensite (structures that do not contain carbides in the grains) in the photographed structure are visually marked, and the area of the ferrite or martensite structure region is determined by image analysis (software name: Nireco's small general-purpose image processing analysis system LUZEX_AP). This operation is performed by measuring and calculating two samples, and the area percentage of ferrite or martensite in this disclosure is determined by averaging them. The total area percentage of bainite and pearlite is determined by subtracting the area percentage of ferrite or martensite from 100.
[0043] In the photographed microstructure, areas that do not contain carbides within the grains are visually marked, and the area of the combined ferrite and martensite regions is determined by image analysis (software name: Nireco's small general-purpose image processing and analysis system LUZEX_AP). This operation is performed by measuring and calculating at least two samples, and the average value is calculated, and this average value is the combined area percentage of the ferrite and martensite structures in this disclosure.
[0044] <Mechanical properties> Tensile strength: 860×F1+450MPa or more, 920×F1+670MPa or less In the steel wire according to the present disclosure, when the contents of C, Si, Mn, and Cr in mass% are (C%), (Si%), (Mn%), and (Cr%), respectively, and F1=(C%)+0.10×(Si%)+0.18×(Mn%)+0.20×(Cr%), the tensile strength is 860×F1+450MPa or more and 920×F1+670MPa or less. When the tensile strength is 860×F1+450MPa or more and 920×F1+670MPa or less, the strength required for machine parts after processing is obtained. The tensile strength is preferably 860×F1+480MPa or more and 920×F1+640MPa or less. Tensile tests of steel wires are performed using JIS Z2241:2011 No. 14A test pieces according to the test method of JIS Z2241:2011 to measure tensile strength (TS), 0.2% yield strength, uniform elongation, and reduction of area. 0.2% yield strength is the stress at which the plastic elongation is 0.2% of the extensometer gauge length, using the offset method defined in JIS Z2241:2011. Tensile test pieces are machined and taken from the steel wires immediately after bending. Tensile tests are performed on three samples, and the average value is used.
[0045] (Tensile strength - 0.2% yield strength) / Uniform elongation: 20+25×(C%) or less The steel wire according to the present disclosure has a (tensile strength-0.2% proof stress) / uniform elongation of 20+25×(C%) or less. By having a (tensile strength-0.2% proof stress) / uniform elongation of 20+25×(C%) or less, workability is improved. (Tensile strength-0.2% proof stress) / uniform elongation is preferably 15+20×(C%) or less. Uniform elongation is the elongation up to the maximum load in a tensile test, and the maximum load displacement is L M When the initial score distance is L0, (L M -L0) / L0×100(%).
[0046] If the martensite fraction of steel wire is high, cracks will occur during bolt forming and the bolt's yield strength ratio will decrease. Even if the total area ratio of ferrite and martensite is reduced, if the (tensile strength - 0.25% yield strength) / uniform elongation of the steel wire is large, the workability when formed into parts will decrease. The reason for this is that in order to increase workability, it is necessary to reduce work hardening, but if the (tensile strength - 0.25% yield strength) / uniform elongation of the steel wire is large, the work hardening will increase and the workability of the steel wire will decrease.
[0047] Aperture: 66-48×(C%) or more The steel wire according to the present disclosure has a reduction of area of 66-48×(C%) or more. The reduction of area of 66-48×(C%) or more improves workability. The reduction of area is preferably 74-48×(C%) or more.
[0048] (diameter) The wire diameter D of the steel wire according to the present disclosure is not particularly limited, but is preferably 2.0 to 22.0 mm, and more preferably 4.0 to 16.0 mm.
[0049] [Machine parts] The mechanical component according to the present disclosure includes a cylindrical shaft portion, Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010 to 0.0150%, and O: Contains 0.003% or less, with the balance being Fe and impurity elements; The mass% contents of C, Si, Mn, Cr, Ni, Mo, and Cu are (C%), (Si%), (Mn%), (Cr%), (Ni%), (Mo%), and (Cu%), respectively, and DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)), the DI is 1.40 or more and 4.50 or less, When the diameter of the shaft portion is d, a total area ratio of ferrite and martensite in a metal structure at a 1 / 4d portion that is a depth of 1 / 4d from the surface of the shaft portion in a cross section perpendicular to the longitudinal direction of the shaft portion is 30.0% or less, When F1=(C%)+0.10×(Si%)+0.18×(Mn%)+0.20×(Cr%), the shaft portion is The tensile strength is 860×F1+450MPa or more and 920×F1+670MPa or less, (tensile strength - 0.2% yield strength) / uniform elongation is 38 + 25 × (C%) or less, 0.2% yield strength / tensile strength is 0.97-0.10×(C%) or more; The aperture is 65-48×(C%) or more.
[0050] The mechanical component according to the present disclosure is obtained by cold forging the steel wire according to the present disclosure described above. Since the chemical composition of the steel wire does not change before and after cold forging, the chemical composition of the machine part is the same as that of the steel wire described above. The optional elements are also the same as the optional components described for the steel wire. The reasons for limiting the content of each element and the preferred range are also the same as those for the steel wire described above.
[0051] In addition, when the mechanical part according to the present disclosure contains an optional element, the DI is calculated according to the B content as follows. When the B content is less than 0.0003%, DI = 0.311 × (C%) 0.5 ×(1+ 0.64×(Si%))×(1+4.10×(Mn%))×(1+2.33×(Cr%))×(1+0.25×(Ni%))×(1+3.14×(Mo%))×(1+0.27×(Cu%)). On the other hand, when the B content is 0.0003 to 0.0050%, DI = 0.311 × (C%) 0.5 ×(1+0.64×(Si%))×(1+4.10×(Mn%))×(1+2.33×(Cr%))×(1+0.25×(Ni%))×(1+3.14×(Mo%))×(1+0.27×(Cu%))×(1+1.5×(0.90-(C%))). Regardless of the B content, the DI value is 1.40 or more and 4.50 or less. The preferred range of DI in mechanical parts is the same as that of the steel wire described above.
[0052] <Metal structure> In the mechanical component according to the present disclosure, when the diameter of the shaft is d, the total area ratio of ferrite and martensite in the metal structure at a 1 / 4d portion that is 1 / 4d deep from the surface of the shaft in a cross section perpendicular to the longitudinal direction of the shaft is 30.0% or less, and the preferred range is also the same as that of the steel wire described above.
[0053] <Mechanical properties> In the mechanical component according to the present disclosure, when the contents by mass of C, Si, Mn, Cr, Ni, Mo, and Cu are (C%), (Si%), (Mn%), (Cr%), (Ni%), (Mo%), and (Cu%), respectively, the shaft portion has the following mechanical properties.
[0054] Tensile strength: 860×F1+430MPa or more, 920×F1+660MPa or less In the mechanical part according to the present disclosure, when F1=(C%)+0.10×(Si%)+0.18×(Mn%)+0.20×(Cr%), the tensile strength of the shaft is 860×F1+430 MPa or more and 920×F1+660 MPa or less. When the tensile strength of the shaft is within this range, the mechanical part has sufficient strength.
[0055] (Tensile strength - 0.2% yield strength) / Uniform elongation: 38+25×(C%) or less The shaft portion of the mechanical component according to the present disclosure has a (tensile strength-0.2% yield strength) / uniform elongation of 38+25×(C%) or less. By having a (tensile strength-0.2% yield strength) / uniform elongation of 38+25×(C%) or less, permanent elongation of the mechanical component is suppressed. The (tensile strength-0.2% yield strength) / uniform elongation is preferably 30+20×(C%) or less. More preferably, it is 23+23×(C%) or less.
[0056] 0.2% yield strength / tensile strength: 0.97-0.10×(C%) or more The shaft portion of the mechanical component according to the present disclosure has a 0.2% yield strength / tensile strength of 0.97-0.10×(C%) or more. By having the 0.2% yield strength / tensile strength of 0.97-0.10×(C%) or more, permanent elongation of the mechanical component is suppressed.
[0057] Aperture: 65-48×(C%) or more The shaft portion of the mechanical component according to the present disclosure has a reduction in area of 65-48×(C%) or more. The reduction in area of 65-48×(C%) or more improves toughness. The reduction in area is preferably 73-48×(C%) or more.
[0058] (diameter) The diameter d of the shaft portion of the mechanical component according to the present disclosure is not particularly limited, but is preferably 2.0 to 22.0 mm, and more preferably 4.0 to 16.0 mm.
[0059] The use of the mechanical component according to the present disclosure is not particularly limited as long as it is a mechanical component that includes a cylindrical shaft portion. Examples of the mechanical component include applications to automotive components having a shaft shape, such as bolts, torsion bars, and stabilizers, and various types of industrial machinery. The mechanical component according to the present disclosure is particularly suitable for automotive and construction bolts, etc.
[0060] [Method of manufacturing steel wire and machine parts] Next, a preferred method for producing the steel wire and the machine component according to the present disclosure will be described. Note that the method for producing the steel wire and the machine component described below is one example for obtaining the steel wire and the machine component according to the present disclosure, and is not limited to the following procedure and method, and any method may be adopted as long as it can realize the steel wire and the machine component according to the present disclosure.
[0061] <Steel wire manufacturing method> A steel slab made of predetermined components that satisfy the above-mentioned chemical composition is heated to 1050 to 1250°C (surface temperature, the same applies below) and held in the furnace for 90 minutes or more. After that, it is hot-rolled at an entry temperature of 750 to 850°C for finish rolling, and then coiled into a ring at 780 to 880°C. If the heating temperature is less than 1050°C or the heating time is less than 90 minutes, the carbide will not be fully dissolved, resulting in a decrease in the yield strength of the machine parts. If the heating temperature exceeds 1250°C, the surface hardness of the machine parts will decrease. If the entry temperature of the finish rolling exceeds 850°C, the crystal grains become coarse and the workability of the steel wire deteriorates. If the entry temperature is less than 750°C, the crystal grain size becomes non-uniform and the yield strength ratio of the mechanical parts decreases. If the coiling temperature exceeds 880°C, the crystal grains become coarse and the workability of the steel wire deteriorates. If the coiling temperature is less than 780°C, the area ratio of ferrite increases and the yield strength ratio of the mechanical parts decreases.
[0062] After coiling, the wire is primarily cooled to 750°C at an average cooling rate of 2 to 15°C / s. After coiling, if the primary cooling rate to 750°C is less than 2°C / s, the crystal grains become coarse and the workability of the steel wire deteriorates. If it exceeds 15°C / s, the recovery and recrystallization of gamma grains is delayed, resulting in mixed grains. As a result, the gamma grain size becomes non-uniform, and the yield strength ratio and permanent elongation of the mechanical parts deteriorate.
[0063] After that, secondary cooling is performed from 750°C to 520°C at an average cooling rate of 25°C / s or more. If the cooling rate from 750°C to 520°C is less than 25°C / s, the area ratio of ferrite increases, and the yield strength ratio of the mechanical part decreases.
[0064] Next, the third cooling is performed from 520°C to 450°C at an average cooling rate of 20°C / s or less. If the average cooling rate from 520°C to 450°C exceeds 20°C / s, the workability of the steel wire deteriorates, and the yield strength ratio and permanent elongation of the mechanical parts deteriorate.
[0065] The wire is then held at 420-460°C for 30-100 seconds (primary holding), heated from 490°C to 550°C at an average heating rate of 10°C / s or more, held at 550-620°C for 60-200 seconds (secondary holding), and then water-cooled to obtain the wire. If the first holding time at 420~460℃ is less than 30 seconds, the yield strength ratio and permanent elongation of the machine parts will deteriorate. If the first holding time exceeds 100 seconds, the value of (tensile strength - 0.2% yield strength) / uniform elongation of the steel wire will increase, and the yield strength ratio and permanent elongation of the machine parts will deteriorate. If the average heating rate from 490°C to 550°C is less than 10°C / s, the mechanical parts will have a deteriorated yield ratio and permanent elongation. If the secondary holding temperature is less than 550°C, the mechanical parts will have a deteriorated yield ratio and permanent elongation, and if it exceeds 620°C, the strength will decrease. If the secondary holding time is less than 60 seconds, the strength ratio and permanent elongation of the mechanical parts will deteriorate, and if it exceeds 200 seconds, the drawing of the steel wire will decrease.
[0066] The obtained wire is surface-treated with zinc phosphate and then drawn in one pass at room temperature using a die with an approach angle of 5° to 14°, with a wire drawing reduction of 12% to 35%, and with the steel wire surface temperature immediately after drawing being 80°C to 200°C. If the approach angle is less than 5°, the reduction of the steel wire will decrease due to heat generated by friction, and if it exceeds 14°, the deformation will be non-uniform and the reduction of the steel wire will decrease. If the wire drawing area reduction rate is less than 12%, the strength of the steel wire will decrease, and if it exceeds 35%, the wire may break during drawing. The surface temperature of the steel wire immediately after drawing was measured with a radiation thermometer on the exit side of the die. If the surface temperature of the steel wire immediately after drawing is less than 80°C, the wire may break due to seizure caused by poor lubrication, and if it exceeds 200°C, the reduction of the steel wire will decrease. After wire drawing, the wire is subjected to aging treatment by holding the wire at 150°C or higher and 250°C or lower for 30 minutes or longer and 180 minutes or shorter. If the aging temperature is less than 150°C, the drawing of the steel wire may decrease, and if it exceeds 250°C, the yield strength ratio of the machine part may decrease. If the aging time is less than 30 minutes or more than 180 minutes, the yield strength ratio and permanent elongation of the machine part may deteriorate.
[0067] The steel wire obtained as described above is subjected to cold heading and rolling to be processed into the shape of a machine part such as a bolt, etc. If necessary, zinc plating and baking treatment are performed.
[0068] The steel wire according to the present disclosure is obtained by drawing the wire rod produced as described above, and plastic flow is observed on the surface layer of the longitudinal section of the steel wire. The steel wire produced using the wire rod has high strength and drawing ability, and is excellent in strength and formability of mechanical parts. The mechanical parts produced using such steel wire have high yield strength ratio and suppressed permanent elongation even if the bluing treatment after forming is omitted. EXAMPLES
[0069] The steel wire and the machine component according to the present disclosure will be described in more detail below with reference to examples. However, the steel wire and the machine component according to the present disclosure are not limited to these examples.
[0070] <Steel wire manufacturing and evaluation> Steels A to X having the composition shown in Table 1 were heated, hot rolled, cooled, and held under the conditions shown in Table 2 to produce wire rods. Thereafter, wire drawing and aging treatment were performed under the conditions shown in Table 3 to produce steel wires. In Table 1, blank spaces indicate that the element was not included, and the balance is Fe and impurities. The blank space for B is "B<0.0003". In each table, underlines indicate that the element is outside the scope of the present disclosure.
[0071] [Table 1]
[0072] [Table 2]
[0073] [Table 3]
[0074] The obtained steel wires were subjected to microstructural observation, tensile tests, and compression tests. Table 4 shows the microstructural and mechanical properties of the steel wires of each test number. For microstructural observation, a cross section perpendicular to the central axis of the steel wire (C cross section) was mirror-polished, etched with picral, and the 1 / 4D portion was observed. The tensile test is performed using JIS Z2241:2011 No. 14A test piece according to the test method of JIS Z2241:2011 to measure the tensile strength (TS), 0.2% yield strength, uniform elongation, and reduction of area. The tensile test piece is taken by machining the steel wire immediately after bending. The tensile test is performed on three samples, and the average value is used. Incidentally, the steel wire of test number 24 was not subjected to the tensile test or compression test since it was broken during drawing.
[0075] For the compression test, a cylindrical test piece with diameter D and height 1.5×D was cut out from the steel wire, and a notch was made parallel to the axial direction of the steel wire on the side of the cylinder. The notch depth was 0.8 mm, the notch angle was 30°, and the R at the notch tip was 0.15. A smooth pressure plate was used to compress the wire in the axial direction and check for cracks. If no cracks were found, the compression ratio was increased by about 1% and compression processing was performed again. The maximum compression ratio at which cracks did not occur was determined as the limit compression ratio. When a crack of 1.0 mm or more occurred in the notch, it was determined that cracks had occurred. Steel wires with a limit compression ratio (%) of 94-0.048×TS (MPa) or more were determined to have good strength and formability.
[0076] [Table 4]
[0077] <Manufacturing and evaluation of machine parts> The steel wires in Table 4 were processed into bolt shapes by cold heading and rolling. Test numbers 1, 4, 8, 9, 11, 13, 14, 15, 19, 21, 23, 24, and 25 were processed into bolt shapes with threads of M6 and shank lengths of 100 mm, while test numbers 2, 3, 5, 6, 7, 10, 12, 16, 17, 18, 20, 22, 26, and 27 were processed into bolt shapes with threads of M8 and shank lengths of 100 mm. After that, electrogalvanization was performed, and after plating, a baking treatment was performed by holding at 200°C for 120 minutes to obtain machine parts (bolts). From the shaft of the obtained machine part (bolt), a sample for microstructural observation and a tensile test piece were taken, and a microstructural observation and a tensile test were performed. The shape of the tensile test piece was a No. 14A test piece of JIS Z2241:2011, and measurements were performed according to the test method of JIS Z2241:2011. The diameter of the parallel part of the tensile test piece was 5 mm for the bolt with M6 thread and 7 mm for the bolt with M8 thread. A proof load test was also performed using the obtained machine part (bolt). Table 5 shows the structure and mechanical properties of the bolt shaft for each test number. In addition, the mechanical part of test number 26 was not subjected to the tensile test and the proof load test because a crack occurred during the bolt processing.
[0078] For microstructural observation, a cross section perpendicular to the central axis of the bolt shaft (cross section C) was mirror-polished, etched with picral, and the 1 / 4d portion was observed. Tensile tests were conducted on bolts to test pieces with threads of M5, parallel sections of 4 mm, and lengths of 70 mm, with gauge lengths of 20 mm and crosshead speeds of 10 mm / min in air at room temperature to measure tensile strength (TS), 0.2% yield strength, and uniform elongation. Tensile tests were conducted on one part (bolt) of each test number. A test piece was judged to be good when the yield strength ratio (0.2% yield strength / tensile strength) was 0.90 or more and the permanent elongation was 1 μm or less.
[0079] The proof load test was performed in the following manner. The shaft of the machine part is processed into a coarse thread shape by rolling or machining. An adapter specified in JIS B1051:2014 is attached to the machine part after thread processing so that the length of the play thread part is equal to the outer diameter of the thread. A tensile stress of 440 MPa is applied in the axial direction for 15 seconds when the tensile strength of the machine part is 600 MPa or more and less than 700 MPa, 515 MPa when it is 700 MPa or more and less than 800 MPa, 580 MPa when it is 800 MPa or more and less than 900 MPa, 650 MPa when it is 900 MPa or more and less than 1000 MPa, 830 MPa when it is 1000 MPa or more and less than 1100 MPa, 910 MPa when it is 1100 MPa or more and less than 1200 MPa, 970 MPa when it is 1200 MPa or more and less than 1300 MPa, and 1050 MPa when it is 1300 MPa or more and less than 1400 MPa. The difference (L1-L0) between the total length L1 of the machine part after unloading and the total length L0 of the machine part before the test is defined as the permanent elongation. The total length L1 of the machine part after unloading and the total length L0 of the machine part before the test were measured with a micrometer.
[0080] [Table 5]
[0081] From the above results, the steel wires of test numbers 1 to 21, which satisfy the requirements of the present disclosure, have excellent formability during bolt processing, and have achieved a high yield strength ratio and suppressed permanent elongation even without performing a bluing treatment after bolt processing. On the other hand, the steel wires of test numbers 23, 25 and 27 had good strength and formability, but the yield strength ratio after bolt processing was insufficient and the permanent elongation was large.
[0082] (Additional Note) The present disclosure includes the following aspects. <1> Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010 to 0.0150%, and O: Contains 0.003% or less, with the balance being Fe and impurity elements; The contents of C, Si, Mn, and Cr in mass% are (C%), (Si%), (Mn%), and (Cr%), respectively. DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)), the DI is 1.4 or more and 4.5 or less, When the diameter of the steel wire is D, the total area ratio of ferrite and martensite in the metal structure at a 1 / 4D part having a depth of 1 / 4D from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire is 30.0% or less, When F1 = (C%) + 0.10 × (Si%) + 0.18 × (Mn%) + 0.20 × (Cr%), the tensile strength is 860 × F1 + 450 MPa or more and 920 × F1 + 670 MPa or less, (tensile strength - 0.2% yield strength) / uniform elongation is 20 + 25 × (C%) or less, A steel wire having a reduction ratio of 66-48×(C%) or more. <2> Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010 to 0.0150%, and O: Contains 0.003% or less, and further contains one or more elements selected from the group consisting of the following A group to D group, with the balance being Fe and impurity elements, [Group A] Ti: 0.050% or less, and B: 0.005% or less of one or two selected from the group consisting of [Group B] Cr: 1.50% or less, Mo: 0.50% or less Nb: 0.050% or less, and V: 0.20% or less, one or more selected from the group consisting of [Group C] Cu: 0.50% or less, Ni: 0.70% or less, Sn: 0.30% or less, and Sb: 0.005% or less, one or more selected from the group consisting of [Group D] Ca: 0.0050% or less The contents of C, Si, Mn, Cr, Ni, Mo, and Cu in mass% are (C%), (Si%), (Mn%), (Cr%), (Ni%), (Mo%), and (Cu%), respectively. When the B content is less than 0.0003%, DI = 0.311 × (C%) 0.5 ×(1+0.64×(Si%))×(1+4.10×(Mn%))×(1+2.33×(Cr%))×(1+0.25×(Ni%))×(1+3.14×(Mo%))×(1+0.27×(Cu%)), When the B content is 0.0003 to 0.005%, DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)) × (1 + 2.33 × (Cr%)) × (1 + 0.25 × (Ni%)) × (1 + 3.14 × (Mo%)) × (1 + 0.27 × (Cu%)) × (1 + 1.5 × (0.90 - (C%))). DI is between 1.4 and 4.5, When the diameter of the steel wire is D, the total area ratio of ferrite and martensite in the metal structure at a 1 / 4D part having a depth of 1 / 4D from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire is 30.0% or less, When F1 = (C%) + 0.10 × (Si%) + 0.18 × (Mn%) + 0.20 × (Cr%), the tensile strength is 860 × F1 + 450 MPa or more and 920 × F1 + 670 MPa or less, (tensile strength - 0.2% yield strength) / uniform elongation is 20 + 25 × (C%) or less, A steel wire having a reduction ratio of 66-48×(C%) or more. <3> Having a chemical composition containing the A group in mass%; <2> The steel wire according to claim 1. <4> Having a chemical composition containing the B group in mass%; <2> or <3> The steel wire according to claim 1. <5> Having a chemical composition containing the C group in mass%; <2> ~ <4> 2. The steel wire according to claim 1 . <6> Having a chemical composition including the D group in mass%; <2> ~ <5> 2. The steel wire according to claim 1 .
[0083] <7> A mechanical component having a cylindrical shaft portion, Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010 to 0.0150%, and O: Contains 0.003% or less, with the balance being Fe and impurity elements; The contents of C, Si, Mn, and Cr in mass% are (C%), (Si%), (Mn%), and (Cr%), respectively, and DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)), the DI is 1.4 or more and 4.5 or less, When the diameter of the shaft portion is d, a total area ratio of ferrite and martensite in a metal structure at a 1 / 4d portion that is a depth of 1 / 4d from the surface of the shaft portion in a cross section perpendicular to the longitudinal direction of the shaft portion is 30.0% or less, The shaft portion is When F1 = (C%) + 0.10 × (Si%) + 0.18 × (Mn%) + 0.20 × (Cr%), the tensile strength is 860 × F1 + 430 MPa or more and 920 × F1 + 660 MPa or less, (tensile strength - 0.2% yield strength) / uniform elongation is 38 + 25 × (C%) or less, 0.2% yield strength / tensile strength is 0.97-0.10×(C%) or more; A mechanical part with a reduction ratio of 65-48×(C%) or more. <8> A mechanical component having a cylindrical shaft portion, Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: Contains 0.003% or less, and further contains one or more elements selected from the group consisting of the following A group to D group, with the balance being Fe and impurity elements; [Group A] Ti: 0.050% or less, and B: 0.005% or less of one or two selected from the group consisting of [Group B] Cr: 1.50% or less, Mo: 0.50% or less Nb: 0.050% or less, and V: 0.20% or less, one or more selected from the group consisting of [Group C] Cu: 0.50% or less, Ni: 0.70% or less, Sn: 0.30% or less, and Sb: 0.005% or less, one or more selected from the group consisting of [Group D] Ca:0.0050% or less The contents of C, Si, Mn, Cr, Ni, Mo, and Cu in mass% are (C%), (Si%), (Mn%), (Cr%), (Ni%), (Mo%), and (Cu%), respectively. When the B content is less than 0.0003%, DI = 0.311 × (C%) 0.5 ×(1+0.64×(Si%))×(1+4.10×(Mn%))×(1+2.33×(Cr%))×(1+0.25×(Ni%))×(1+3.14×(Mo%))×(1+0.27×(Cu%)), When the B content is 0.0003 to 0.005%, DI = 0.311 × (C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)) × (1 + 2.33 × (Cr%)) × (1 + 0.25 × (Ni%)) × (1 + 3.14 × (Mo%)) × (1 + 0.27 × (Cu%)) × (1 + 1.5 × (0.90 - (C%))). DI is between 1.4 and 4.5, When the diameter of the shaft portion is d, a total area ratio of ferrite and martensite in a metal structure at a 1 / 4d portion that is a depth of 1 / 4d from the surface of the shaft portion in a cross section perpendicular to the longitudinal direction of the shaft portion is 30.0% or less, The shaft portion is When F1 = (C%) + 0.10 × (Si%) + 0.18 × (Mn%) + 0.20 × (Cr%), the tensile strength is 860 × F1 + 430 MPa or more and 920 × F1 + 660 MPa or less, (tensile strength - 0.2% yield strength) / uniform elongation is 38 + 25 × (C%) or less, 0.2% yield strength / tensile strength is 0.97-0.10×(C%) or more; A mechanical part with a reduction ratio of 65-48×(C%) or more. <9> Having a chemical composition containing the A group in mass%; <8> A mechanical part as described in. <10> Having a chemical composition containing the B group in mass%; <8> or <9> A mechanical part as described in. <11> Having a chemical composition containing the C group in mass%; <8> ~ <10> 2. A mechanical part according to claim 1 . <12> Having a chemical composition including the D group in mass%; <8> ~ <11> 2. A mechanical part according to claim 1 .
[0084] The disclosure of Japanese Patent Application No. 2023-059431, filed on March 31, 2023, is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described herein are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually indicated to be incorporated herein by reference.
Claims
1. In mass percent, C: 0.08-0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005-0.080%, N: 0.0010-0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0 to 0.20%, Cu: 0 to 0.50%, Ni: 0 to 0.70%, Sn: 0 to 0.30%, Sb: 0 to 0.005%, and Ca: 0-0.0050%, and the balance being Fe and impurity elements, The contents of C, Si, Mn, Cr, Ni, Mo, and Cu in mass% are (C%), (Si%), (Mn%), (Cr%), (Ni%), (Mo%), and (Cu%), respectively; (I) the chemical composition is, in mass%, C: 0.08-0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005-0.080%, N: 0.0010 to 0.0150%, and O: 0.003% or less, with the balance being Fe and impurity elements, DI=0.311×(C%) 0.5 ×(1+0.64×(Si%))×(1+4.10×(Mn%))とし、 (II) the chemical composition is, in mass%, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0 to 0.20%, Cu: 0 to 0.50%, Ni: 0 to 0.70%, Sn: 0 to 0.30%, Sb: 0 to 0.005%, and Ca: 0-0.0050%, and the B content is less than 0.0003%, 4094003111×(3%) 0.5 ×(1000.644×(35%))×(1+4.10 ×(70%))×(10+2.33×(31%))× (1000.25×(80%))×(1+3.14× Mo)))×(1+00.27)))とし、 (III) The chemical composition, in mass%, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0 to 0.20%, Cu: 0 to 0.50%, Ni: 0 to 0.70%, Sn: 0 to 0.30%, Sb: 0 to 0.005%, and Ca: 0-0.0050%, and the B content is 0.0003 to 0.0050%, DI=0.311×(C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)) × (1 + 2.33 × (Cr%)) × (1 + 0.25 × (Ni%)) × (1 + 3.14 × (Mo%)) × (1 + 0.27 × (Cu%)) × (1 + 1.5 × (0.90 - (C%))). DI is 1.40 or more and 4.50 or less, When the diameter of the steel wire is D, a total area ratio of ferrite and martensite in a metal structure at a 1 / 4D portion having a depth of 1 / 4D from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire is 30.0% or less, When F1 = (C%) + 0.10 × (Si%) + 0.18 × (Mn%) + 0.20 × (Cr%), the tensile strength is 860 × F1 + 450 MPa or more and 920 × F1 + 670 MPa or less, The value of (tensile strength-0.2% proof stress) / uniform elongation is 20+25×(C%) or less, A steel wire having a reduction in area of 66-48×(C%) or more.
2. The steel wire according to claim 1, wherein a total area ratio of bainite and pearlite in the metal structure at the ¼ D portion is 70.0% or more.
3. A mechanical component having a cylindrical shaft portion, In mass percent, C: 0.08-0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005-0.080%, N: 0.0010-0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0 to 0.20%, Cu: 0 to 0.50%, Ni: 0 to 0.70%, Sn: 0 to 0.30%, Sb: 0 to 0.005%, and Ca: 0-0.0050%, The balance has a chemical composition consisting of Fe and impurity elements, The contents of C, Si, Mn, Cr, Ni, Mo, and Cu in mass% are (C%), (Si%), (Mn%), (Cr%), (Ni%), (Mo%), and (Cu%), respectively; (I) the chemical composition is, in mass%, C: 0.08-0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005-0.080%, N: 0.0010 to 0.0150%, and O: 0.003% or less, with the balance being Fe and impurity elements, DI=0.311×(C%) 0.5 ×(1+0.64×(Si%))×(1+4.10×(Mn%))とし、 (II) the chemical composition is, in mass%, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0 to 0.20%, Cu: 0 to 0.50%, Ni: 0 to 0.70%, Sn: 0 to 0.30%, Sb: 0 to 0.005%, and Ca: 0-0.0050%, and the B content is less than 0.0003%, 4094003111×(3%) 0.5 ×(1000.644×(35%))×(1+4.10 ×(70%))×(10+2.33×(31%))× (1000.25×(80%))×(1+3.14× Mo)))×(1+00.27)))とし、 (III) The chemical composition, in mass%, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0 to 0.20%, Cu: 0 to 0.50%, Ni: 0 to 0.70%, Sn: 0 to 0.30%, Sb: 0 to 0.005%, and Ca: 0-0.0050%, and the B content is 0.0003 to 0.0050%, DI=0.311×(C%) 0.5 × (1 + 0.64 × (Si%)) × (1 + 4.10 × (Mn%)) × (1 + 2.33 × (Cr%)) × (1 + 0.25 × (Ni%)) × (1 + 3.14 × (Mo%)) × (1 + 0.27 × (Cu%)) × (1 + 1.5 × (0.90 - (C%))). DI is 1.40 or more and 4.50 or less, When the diameter of the shaft portion is d, a total area ratio of ferrite and martensite in a metal structure at a 1 / 4d portion that is a depth of 1 / 4d from the surface of the shaft portion in a cross section perpendicular to the longitudinal direction of the shaft portion is 30.0% or less, The shaft portion is When F1 = (C%) + 0.10 × (Si%) + 0.18 × (Mn%) + 0.20 × (Cr%), the tensile strength is 860 × F1 + 430 MPa or more and 920 × F1 + 660 MPa or less, The value of (tensile strength-0.2% proof stress) / uniform elongation is 38+25×(C%) or less; 0.2% proof stress / tensile strength is 0.97-0.10×(C%) or more; A mechanical part having a drawing ratio of 65-48×(C%) or more.
4. The mechanical component according to claim 3 , wherein a total area ratio of bainite and pearlite in the metal structure at the ¼ d portion is 70.0% or more.
Citation Information
Patent Citations
Manufacture of steel wire rod for non-heat treated bolt
JP1990166229A
Non-refined steel material for weld bolt and method for producing the same
JP2015190002A
Steel wire, wire for non-heat-treated mechanical components, and non-heat-treated mechanical component
JP2021183710A
Wire material for non-refined machine component; steel wire for non-refined machine component; non-refined machine component; and method for manufacturing wire material for non-refined machine component, steel wire for non-refined machine component, and non-refined machine component
WO2013031640A1
Rod material for non-tempered machine component, steel rod for non-tempered machine component, and non-tempered machine component
WO2016121820A1